Cryoballoon ablation for atrial fibrillation guided by real-time three-dimensional transoesophageal echocardiography : a feasibility study - L. Ottaviano; G. Chierchia; N. Bruno; A. Antonelli; A. T. A. Alsheraei; A. M. Porrini; E. Gronda; A. Duijnhower; P. Brugada; A. S. Montenero; A. Bregasi; F. Donatelli (EP Europace, 2013)
Aims Cryoballoon ablation (CBA; Arctic Front, Medtronic) has proven very effective in achieving pulmonary vein isolation. Real-time three-dimensional transoesophageal echocardiography (RT 3D TEE) is a novel technology, which permits detailed visualization of cardiac structures in a 3D perspective. The aim of the present study was to assess the feasibility, advantages, and safety of RT 3D TEE in guiding CBA in a series of patients affected by paroxysmal atrial fibrillation. Methods and results Forty-five patients (34 males, mean age: 63 ± 12 years) underwent CBA guided by 3D TEE. A total of 190 veins could be documented by TEE. Real-time three-dimensional transoesophageal echocardiography successfully guided the operator to position the CB in the pulmonary vein (PV) ostium and obtain complete occlusion in all 190 (100%) veins. Transoesophageal echocardiography identified leakages in 25 (13%) veins led to successful elimination of PV–left atrium (LA) backflow by guiding correct balloon repositioning. In four (2%) veins, this imaging tool led to perform successful pull-down manoeuvres. After a mean 2.6 ± 1.4 applications, isolation could be documented in 190 (100%) PVs. Median procedural and fluoroscopy times were 145 and 24 min. During a median follow-up of 278 days, 37 (82%) patients did not experience atrial fibrillation recurrence following a 3-month blanking period. Conclusion Cryoballoon ablation is safe and feasible under RT 3D TEE guidance. This imaging tool permits perfect visualization of all PV ostia and neighbouring LA structures. Most importantly, it proved very efficient in guiding the operator to achieve complete occlusion and successful isolation in all veins.